The emergence of atheism in post-colonial South Africa - Pillay, Patrick Brian Segaren (University of KwaZulu-Natal, 2017)
This study aims to offer an account of the emergence of the phenomenon of atheism in South Africa and in so doing present a case for its admittance as a new and exciting field of research within the academy in the country. The pervasive assumptions of religious normativity on the continent and in South Africa may serve to conceal a rich and vibrant worldview of atheism which, as this study proposes, can in its own right, also attempt meaningful responses to life’s deepest and most complex questions, without the need to declare an affiliation to any religious authority or sect. It is in the lived realities of atheists and in the makings of their social contexts, inclusive of its political history, its media and its laws, that this study finds its mooring and academic purpose. Given the embryonic nature of this project within a field of study which is under-researched in the country, the research design adopted includes a set of empirical components, by way of direct interviews with a set of self-pronounced South African atheists, an analysis of the phenomenon in relation to the country’s legal framework and jurisprudence, and a survey of the online digital media contexts in which atheism also finds representation. This multi-disciplinary approach sought to broadly trace through factors historic and current, as well as issues foreign and domestic, which have either advanced or suppressed the emergence of atheism in South Africa. Locating this study within the historical development of the worldview of atheism from as far back as Greek antiquity up to advances made in recent years in shaping this field of formal academic research, was considered imperative as a potential gateway for new rounds of future research on atheism itself, or other related sub-categories within the broader field of non-religion. Constructs which are distinctly different but which have grown in alliance with atheism in recent years, such as secularity and humanism have also become essential to the construction of atheist self-identities and the emergence of atheism as a social phenomenon in South Africa. The dialogue developed within this study between related literature resources and the responses of interviewees pointed to a new range of perspectives on atheism which were greater than the sum of these parts, in that South African atheists had demonstrably moved beyond the confines of having their lives defined by the absence of a religious belief system or by something that they are not.
free